IMPLEMENTASI PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN PARTISIPASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI SMP NEGERI 14 SEMARANG - Anggaeningati, Melisa Selly; Purwosaputro, Supriyono; Suneki, Sri (FPIPSKR Universitas PGRI Semarang, 2024)
This research was motivated by the fact that some students did not pay attention to the explanation of the material delivered by the teacher, students preferred to listen to the explanation of the material rather than express opinions, and students did not actively ask the teacher or students when learning in class. The formulation of the research problem is how to implement problem-based learning in increasing student learning participation in Pancasila Education subjects at SMP Negeri 14 Semarang. The type of research used is qualitative research with a descriptive approach. Data collection techniques include observation, interviews and documentation. The data analysis techniques for this research are data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that the preparations carried out by teachers before teaching are that teachers choose background material on the history of the birth of Pancasila and create open modules based on the independent curriculum. Implementation of problem-based learning includes the teacher asking students to read material about the historical background of the birth of Pancasila, the teacher forming students into 8 groups, the teacher conditioning students to complete group assignments, students presenting the results of group work, and the teacher listening by confirming or adding answers to the results of group work . Student learning participation in implementing problem based learning such as students paying attention to explanations of material, students asking questions, students being able to express opinions, listening to other students' opinions in group discussions, and being able to do group assignments. Obstacles include students not being responsive to the environment, lack of time, less conducive classes, illness, and students not being familiar with the learning model used. After carrying out this research, it was concluded that the application of problem-based learning was sufficient to increase student learning participation.